2020
DOI: 10.1590/1808-1657000802018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the type of milking on mammary gland examination in Saanen goats

Abstract: This research evaluated the effect of milking on the physical exam of the mammary gland (MG) and milk examination in Saanen goats. Six properties were selected, four farms were used after evaluation of criteria selection and distributed in two groups according to the milking method: manual or mechanical. The physical examination of MG was performed using the techniques of inspection and palpation, in addition to the examination of the milk by strip cup, California Mastitis Test, somatic cell count, and bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…A recent study conducted on Saanen goats showed that the type of milking influenced both the physical parameters of the mammary gland and the milk characteristics. Therefore, mechanical milking was associated with a higher MSCC count (0.787 × 10 6 cells/mL) compared to manual milking (0.350 × 10 6 cells/mL) and, nevertheless, a greater consistency of the mammary gland was reported in mechanical milked goats [83]. Furthermore, some authors established a link between the use of automatic valve cups during mechanical milking and the risk of mastitis, with a higher MSCC at the beginning of lactation [84].…”
Section: Extrinsic Factorsmentioning
confidence: 87%
“…A recent study conducted on Saanen goats showed that the type of milking influenced both the physical parameters of the mammary gland and the milk characteristics. Therefore, mechanical milking was associated with a higher MSCC count (0.787 × 10 6 cells/mL) compared to manual milking (0.350 × 10 6 cells/mL) and, nevertheless, a greater consistency of the mammary gland was reported in mechanical milked goats [83]. Furthermore, some authors established a link between the use of automatic valve cups during mechanical milking and the risk of mastitis, with a higher MSCC at the beginning of lactation [84].…”
Section: Extrinsic Factorsmentioning
confidence: 87%
“…Udder health in small ruminants also relies on visual assessments, with literature determining that healthy udders should be properly attached to the animal's abdomen and have a large volume and rounded shape, which are ideal for milk production (Vrdoljak et al, 2020). Palpation is also a crucial part of the mammary gland examination in ruminants such as goats, which can aid to identify if there is an inadequate use of milking equipment in dairy goat farms (Ramos et al, 2020).…”
Section: Physical Assessmentmentioning
confidence: 99%
“…The cause of this problem is the lack of a suitable milking machine adapted to the physiology of the udders of sheep and goats. Studies on Saanen goats in Sao Paulo have shown that if the correct milking machine meeting the udder requirement is not used, negative effects on udder properties and poor milk quality can be found [24]. Katanos et al [15] emphasized that the best machine milking technique is routine milking without applying hand stripping in dairy goats.…”
Section: Introductionmentioning
confidence: 99%